Definition and understanding of “efficiency” in healthcare provision research: a scoping review - Lötscher-Stamm, Mélanie; Lenzin, Golda (Frontiers in Public Health, 2024)
Background: With rising healthcare costs over the last decades, the concept of efficiency has gained popularity in healthcare provision research. As efficiency can be understood and measured in many different ways, it is often unclear what is meant by “efficient health systems” or “efficient healthcare providers”. Objectives: This study aims to analyze and categorize the different definitions and understandings of “efficiency” used in healthcare provision research over time. Methods: We searched five databases (Medline, Embase, CINAHL, Business Source Premier, and EconLit) to conduct a scoping review. Sources were screened independently by two researchers, using the online software Rayyan. Results are reported using PRISMA-ScR. Results: Of 1441 individual sources identified, 389 were included in the review. Most papers (77.3%) using the term “efficiency” do not include explicit definitions or explanations of their understanding of it. Almost all papers (99.0%) are interested in productive efficiency (vs. allocative efficiency) and more specifically technical efficiency, therefore comparing the number of inputs used and outputs produced. While many papers (70.4%) include some elements of quality of care or health outcomes in their discussion, few (30.3%) include aspects of quality in their measurement of efficiency. Over the last decades, Data Envelopment Analysis has become the main method to measure efficiency. We propose a broad categorization of efficiency definitions that could be used by researchers to improve the comprehensibility and comparability of their research. Key features are the general type of efficiency, inclusion of quality or outcome information, and inclusion of cost information. Discussion: To allow for better comparability and comprehensibility, researchers in healthcare provision should state explicitly which type of efficiency they are studying. To do this, we propose to use combinations of the terms productive efficiency, allocative efficiency, quality-inclusive efficiency, and cost efficiency.